Popyt na wykształcenie oraz korzyści i koszty wykształcenia - Tyc, Waldemar (Educational demand and benefits and costs of education, 2006)
The article discusses factors affecting educational demand as well as benefits and costs of education. It presents relations between levels of education and income and between education level and unemployment. Furthermore, it includes principles of balancing the graduate employment market as well as external benefits of education.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 330-341